In vivo splicing of the premRNAs from early region 3 of adenovirus-2: association of precursors, intermediates and products with hnRNP. - Gallinaro, H (1986)
To elucidate the function of hnRNP in the splicing of premRNA, we studied the distribution of the transcripts from the early region 3 of adenovirus-2 in hnRNP from infected HeLa cells. In addition to premRNAs and mRNAs, we detected excised IVS 1 and the products of cleavage of premRNA at the 5' splice site of IVS 1 (free leader 1 and IVS 1-exon 2). All these molecules were present in hnRNP and persisted in the salt-resistant complexes after a 400 mM KCl treatment. None of them was exclusively part of the salt dissociable monoparticles. The precursors, intermediates and products of the splicing reaction were associated with both monoparticles and salt resistant complexes. This eliminates the possibility that one of the classes of RNP is exclusively involved in one of the steps of RNA processing. Whereas the size of hnRNP was related to that of its RNA for most molecules, the small molecules free leader 1 and excised IVS 1 were found in the large hnRNP containing premRNA as well as in small size hnRNP. A probable interpretation of these results is that the cleavage products are associated with the premRNP complex immediately after cleavage and are then released in the form of an individual RNP.